THE CONCEPT OF CHILD EDUCATION (A CIRITICAL REVIEW IN ACCORDANCE WITH AL-QUR’AN AND HADITS) - Tauhiq Tauhiq (JICSA : Journal of Islamic Civilization in Southeast Asian, 2022)
This study aims to find out the urgency of children's education according to Islamic views and to explore the concept of children's education according to the Qur'an and hadits. The research uses a deductive thinking approach, namely research that starts from general statements and draws specific conclusions, in the form of narrative descriptions. The results of the study show that the Qur'an and al-Hadith have a very perfect concept of child education, therefore it is fitting for everyone involved in this education to understand these concepts well, including parents as the main person in charge. in the process of educating children, they should have sufficient provisions or preparation both physically and spiritually, psychologically, and mentally as well as scientific preparation in managing the household and as Mu'allim (teacher) in the family.